Media Articulate Storyline Based on the Values of the Rokat Phandaba Tradition in Students at SMAN 1 Grujugan Bondowoso - Triyanto, Jefri Rieski (Indonesian Journal of History Education, 2023)
The aims of this study are as follows: (1) to analyze and find out the needs of historical learning media based on local wisdom values at SMAN 1 Grujugan; (2) to understand the procedure for developing an articulate storyline media based on the traditional values of the Rokaat Phandeba; 3) Knowing the feasibility of the media articulate storyline that was developed based on the results of expert validation. This type of research is development or research and development by adopting the ADDIE model design (analysis, design, development, implementation, and evaluation) in the product development process. The results of this study indicate that the history learning media used at SMAN 1 Grujugan still uses conventional media such as PowerPoint and only uses material from textbooks and internet sources. Second, the development of articulate storyline media was developed based on the primary sources of material from Rokat Phandaba by adopting the ADDIE model, starting from analyzing the needs of learning media in the field, making media designs developed, developing media articulate storylines based on the results of material validation tests and media validation tests by experts, implementation limited and broad. The final step is to evaluate the media that was developed based on the results of the questionnaires given by students and teachers. Based on the validation results of learning media experts and material experts, the following percentages were obtained: (1) good 60%; (2) 10% is sufficient; (3) perfect 0%; (4) less than 0%; (5) significantly less 0%.